Regional importance of Mittelstand firms and innovation performance - Michael Berlemann; Vera Jahn (Verein für Socialpolitik, Ausschuss für Wirtschaftssysteme und Institutionenökonomik, 2015)
Despite of the deeply rooted belief of politicians from all over the world in the important role of Mittelstand firms, there has been surprisingly little empirical research on this issue, yet. This article contributes to the literature by studying whether the relative regional importance of Mittelstand firms has an effect on regional innovation performance. Using a cross section of German NUTS-3-regions, a significantly positive relation between the relative importance of owner-managed SMEs and patent applications is identified. This finding is highly robust when controlling for spatial correlations as they often occur in highly disaggregated regional analyses.
Keywords: O31; C21; D23; 330; Innovation; Mittelstand firms; Owner-management; SMEs; Germany